ANALYSIS OF HYPERACTIVE CHILD BEHAVIOR AND HANDLING EFFORTS IN EDUCATION - Abidin, Mustika (IAIN Ambon, 2023)
Abstract: This study discusses the analysis of hyperactive children's behavior and efforts to handle it in education through the literature review method. The behavior of hyperactive children is a child who experiences attention deficit disorder which is characterized by frequent movements and this can affect the child's psychological, physical, and social problems. The impact of hyperactive behavior has an impact on the children themselves and the environment. Handling in overcoming the behavior of hyperactive children is by doing therapy such as drug therapy, music therapy, play therapy, consulting with child psychologists, taking time for children, providing adequate and appropriate affection, not always meeting the child's demands, giving adequate attention. adequate for children, monitor children at all times, and guide them in learning, parents and teachers must examine and understand children, be patient in caring for children, train their focus and raise children's confidence. The need to establish good communication relationships between parents, teachers, and schools by assigning tasks that ensure the success of children.Abstrak: Penelitian ini membahas analisis mengenai perilaku anak hiperaktif dan upaya penanganannya dalam pendidikan melalui metode tinjauan literatur. Perilaku anak hiperaktif adalah anak yang mengalami gangguan pemusatan perhatian yang ditandai dengan seringnya melakukan gerakan dan hal tersebut dapat mempengaruhi psikis, fisik, maupun masalah sosial anak. Dampak yang ditimbulkan dari perilaku hiperaktif yaitu berdampak bagi diri anak sendiri maupun lingkungan. Penanganan dalam mengatasi perilaku anak hiperaktif yaitu dengan melakukan terapi seperti terapi obat-obatan, terapi musik, terapi bermain, berkonsultasi dengan ahli psikolog anak, meluangkan waktu untuk anak, memberikan kasih sayang yang memadai dan tepat, tidak selalu memenuhi tuntutan anak, memberikan perhatian yang memadai kepada anak, memantau anak setiap saat, dan membimbing mereka dalam belajar, orang tua dan guru harus memeriksa dan memahami anak, sabar dalam merawat anak, melatih fokusnya dan membangkitkan kepercayaan diri anak. Perlunya menjalin hubungan komunikasi yang baik antara orang tua, guru, dan sekolah dengan memberikan tugas-tugas yang menjamin keberhasilan anak-anak.